COLLABORATION OF INTERNATIONAL FINANCIAL INSTITUTIONS WITH POST-CONFLICT COUNTRIES (International Journal of Innovative Technologies in Economy, 2018)
The article is dedicated to the role of international financial institutions in overcoming the consequences of war actions. The author studies the evolution of the role of international financial institutions in the post-conflict renewal during the second half of ХХ century and at the beginning of ХХI century; the author also reveals the change of its key emphasis in the cold war period and after the war end.The article determines the main negative consequences in the activity of international financial institutions on the issue of overcoming the consequences of war conflicts that are the following: increasing the debtor’s sovereign loading, the priority support of the branches, which are the most interesting for foreign investors, the interference in inner policy, the contribution to corruption, and in some cases, the worsening of ecological situation in post-conflict countries. A special attention is paid to the issue of odious debt and the practice of refusal of debtor’s obligations of previous regimes in a post-conflict period.The article deals with the conflict of interests of international financial institutions and the management of the countries suffered from war actions concerning the mobilization of inner resources and providing external financial support from the position of the theory of plays, that makes it possible to reveal the reasons of the slow post-conflict renewal.